Young adults with migration background: mental health problems, risk behaviour, and educational and occupational development. Results of an 18-year longitudinal study - Wolfgang Schulz; Max Supke; Kurt Hahlweg; Ann-Katrin Job (International Journal of Adolescence and Youth)
The few German studies on children, adolescents, and young adults with a migration background (MB) suggest a slightly greater burden compared to those without an MB. This difference is likely influenced by risk factors such as poorer living conditions and lower socio-economic status (SES). This study compares children with and without an MB (N = 316) at three assessment points over 18 years regarding mental health problems, substance use behaviour, and school and professional qualifications: in kindergarten, adolescence, and young adulthood. Young adults with an MB exhibited significantly more symptoms of depression and anxiety, poorer mental health, less social support, and more frequent risky alcohol and tobacco use compared to those without an MB. These differences persisted even when controlling for SES. The MB was found to be the most important predictor of mental health problems in young adulthood. Future studies should consider the heterogeneity of migrants.